2022
DOI: 10.1183/13993003.01306-2022
|View full text |Cite
|
Sign up to set email alerts
|

GPR183 antagonism reduces macrophage infiltration in influenza and SARS-CoV-2 infection

Abstract: RationaleSevere viral respiratory infections are often characterised by extensive myeloid cell infiltration and activation and persistent lung tissue injury. However, the immunological mechanisms driving excessive inflammation in the lung remain poorly understood.ObjectivesTo identify the mechanisms that drive immune cell recruitment in the lung during viral respiratory infections and identify novel drug targets to reduce inflammation and disease severity.MethodsPreclinical murine models of influenza virus and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…In contrast, more recently Fessler et al [37] using transgenic mice expressing human ACE2 under the epithelial K18 promoter and infected with the USA-WA1/2020 SARS-CoV-2 strain, revealed that 25-OHC did not modify viral clearance from the lungs. Similar to the study presented here [9], Fessler et al also reported upregulation of Ch25h in the lungs of mice infected with SARS-CoV-2 [37]. In contrast however, using the transgenic human ACE2 mice and the USA-WA1/2020 SARS-CoV-2 strain, Fessler et al [37] did not observe any effect on SARS-CoV-2 clearance or disease outcome following treatment with GPR183 antagonism, which may be a facet of both the mouse and viral strains used.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…In contrast, more recently Fessler et al [37] using transgenic mice expressing human ACE2 under the epithelial K18 promoter and infected with the USA-WA1/2020 SARS-CoV-2 strain, revealed that 25-OHC did not modify viral clearance from the lungs. Similar to the study presented here [9], Fessler et al also reported upregulation of Ch25h in the lungs of mice infected with SARS-CoV-2 [37]. In contrast however, using the transgenic human ACE2 mice and the USA-WA1/2020 SARS-CoV-2 strain, Fessler et al [37] did not observe any effect on SARS-CoV-2 clearance or disease outcome following treatment with GPR183 antagonism, which may be a facet of both the mouse and viral strains used.…”
supporting
confidence: 84%
“…25-OHC can then be metabolized further by 25-OHC 7α-hydroxylase (CYP7B1) to 7α,25-OHC that contains an additional hydroxyl group at position 7α [22]. 7α,25-OHC has been described as the predominant ligand for GPR183 [11,12], as examined in this current study by Foo et al where it regulated macrophage recruitment to the lungs [9]. GPR183 is a G protein-coupled receptor expressed on monocytes, macrophages [23] and lymphocytes where it guides B cell movement along the T-B cell border and through B cell follicles of secondary lymphoid organs [24,25] and CD4 T cell positioning within lymph nodes [26].…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Five out of six genes show a positive role in the inflammation process: CXCL8 (interleukin-8) is a member of the chemokine family involved in cell recruitment and activation under inflammatory conditions 21 ; EREG is a pro-inflammatory gene with a role in tissue healing and vascularization 22 ; JUN and FOS are two genes expressed in monocytes and macrophages involved in promoting inflammation 23,24 , and both are included as markers in a recently general inflammatory macrophage activation phenotype encompassing responses to HIV, sepsis, and SARS-CoV-2 25 ; CCL3 is a pro-inflammatory gene and one of the major HIV-suppressive factors produced by CD8+ T-cells and monocytes 25,26 . Other proinflammatory genes appear among the top underexpressed genes (Table 1): GPR183 plays a role in attracting macrophages during viral inflammation 27 ; MIR23AHG is a long non-coding RNA gene promoting inflammation polarization in macrophages 28 and associated to chronic inflammation in ulcerative colitis 29 ; TIPARP is an antiviral gene, with a specific anti-HIV-1 effect in monocytes 30 ; NAMPT is a gene involved in the inflammatory responses activation with cytokine-like behavior 31 ; IL1B is a pro-inflammatory cytokine 32,33 ; and KLF6 is known to regulate macrophage polarization towards the proinflammatory phenotype 34 . In summary, five out of six DEGs and several of the top underexpressed genes are markedly involved in inflammatory processes of myeloid cells.…”
Section: Resultsmentioning
confidence: 99%